Opinion of fishermen towards their well-being under Agricultural Diversification and Intensification Project (ADIP) in Bangladesh - Mahmud, Kazi Tanvir; Mohammed, Zainal Abidin; Sambasivan, Murali; Khan, Sardana Islam (Faculty of Economics and Management, Universiti Putra Malaysia, 2010)
Agricultural Diversification and intensification Project (ADIP) was the collaborative program of the Government of Bangladesh (GOB ) and donor agencies. The program was implemented in four district of Bangladesh in order to upgrade the living-standard of the poor people who were engaged in agricultural activities. This study took the initiative to assess the impact of microcredit on the living-standard in terms of household expenditure of the borrowers under ADIP’s fishery program. Primary data was collected from landless and marginal borrowers through a simple random sampling technique from the project areas who took loan for the first time for fisheries activities. Weighted Least Square (WLS) technique was used to examine the influence of socioeconomic variables on the dependent variable “household total expenditure”. The study shows that six variables such as household’s income, years of schooling of the borrowers, training, investment on fishery activities, expenditure on food, distance of rural market from borrower’s dwelling place were significantly related to the household’s total expenditure. The study also indicates that the fishery credit did not have any significant influence on borrowers’ living-standard in terms of household’s total expenditure.